2014
DOI: 10.1016/j.ophtha.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Objective Measurement of Vitreous Inflammation Using Optical Coherence Tomography

Abstract: Purpose To obtain measurements of vitreous signal intensity from optical coherence tomography (OCT) image sets in patients with uveitis, with the aim of developing an objective, quantitative marker of inflammatory activity in patients with this disease. Design Retrospective, observational case-control series. Participants Thirty patients (30 eyes), with vitreous haze secondary to intermediate, posterior, or panuveitis; twelve patients (12 eyes) with uveitis but without evidence of vitreous haze; and 18 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
124
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(132 citation statements)
references
References 43 publications
4
124
2
2
Order By: Relevance
“…AC cell grade and VH grade). 36 The SUN system was a formalisation and adoption of the Nussenblatt scale. 8,37 Grading requires the examination of a patient's eye by an indirect ophthalmoscope followed by a comparison of the appearance with a series of photographs of varying grades of fundus VH.…”
Section: Measurement Of Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…AC cell grade and VH grade). 36 The SUN system was a formalisation and adoption of the Nussenblatt scale. 8,37 Grading requires the examination of a patient's eye by an indirect ophthalmoscope followed by a comparison of the appearance with a series of photographs of varying grades of fundus VH.…”
Section: Measurement Of Diseasementioning
confidence: 99%
“…8,37 Grading requires the examination of a patient's eye by an indirect ophthalmoscope followed by a comparison of the appearance with a series of photographs of varying grades of fundus VH. 37 Although the grading system is accepted by the US Food and Drug Administration and has been used in a number of recent studies of uveitis, 36 it is a subjective grading of cloudiness in the vitreous humour caused by inflammatory cells and cell debris on a non-continuous scale (0, 0.5+, 1, 2, 3 and 4+). 7,8,34,37 Its poor discriminatory property for detecting changes in the lower VH grades and extensive inter-rater variations have been reported to be limitations of this system.…”
Section: Measurement Of Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Although pixel intensity has been used to characterize fluid particulate in other OCT applications [30], it is nevertheless not ideal in analyzing mucus due to the fact that dense and heterogeneous distributions of mucus can cause strong scattering effects that can impact the accuracy of the measurements. To compensate for this, we calculate a second-order statistic based on the occurrences of relationships between local pixel pairs using GLCM Contrast.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Several early studies have indicated how OCT-derived choroidal images can be useful in uveitic disorders. For example, OCT has been used (1) to describe characteristic features of specific uveitis entities, including thinning of Haller's large vessel layer of the choroid in idiopathic panuveitis and extra-macular choroidal changes in birdshot chorioretinopathy; 18,19 (2) to identify distinct stages of a disease process as illustrated by punctate inner choroidopathy; 20,21 (3) objective measurement of vitreous inflammation; 22 and (4) to monitor response to therapy, exemplified by a reduction of subfoveal choroidal thickening with corticosteroid therapy in Vogt-KoyanagiHarada disease. 23 Additionally, the potential of OCT angiography in uveitic diseases has yet to be realised.…”
Section: Introductionmentioning
confidence: 99%